Lithuanian TV drama adaptation and the convergence of the media aspect (1957–1967) - Pečiulis, Žygintas (Information & Media, 2015)
TV has expanded the audiovisual media opportunities directly spreading the image and sound to the mass audience. Discussions are taking place: to create an independent TV content, or will other media (music, theater, cinema) be re-broadcasters. The first decade of the Lithuanian television (1957–1967) was the time of controversial experiments of the TV aesthetic principles. Technological characteristics (live broadcast, a small black-and-white TV screen) and a specific audience (looking in the home environment) led to the intimacy of performance. On the other hand, the TV was associated with cinema resolution (angles, montage), so the television performances were inserted elements of cinematography. TV was looking for new ways to literary adaptation. Attempts were made to keep the text of the work, the author's thoughts. A specific early television feature was different forms of expression in a television program. Dramatic elements were inserted in documentary programs simulating live reporting. We see efforts to find distinctive adaptation techniques (intimacy of performance, the desire to read a literary work, drama and documentary television program clusters). It was a time of self-perception of the new media, which later allowed to find a specific expression of the TV form and genre (fiction series, games, reality formats, entertainment shows).
Keywords: ...